Biotic elicitor mediated induction of systemic resistance in cabbage – Xanthomonas campestris pv. campestris system - Barman, A Roy; Dutta, S (Indian Journal of Plant Protection, 2020)
Black rot disease caused by Xanthomonas campestris pv. campestris (Xcc) has become a menace to the cultivation of cabbage and other cole crops in West Bengal due to seed-borne infection from exotic seed materials, congenial weather condition, scarcity of resistant sources and progressive development of resistance to commercially available antibiotics. Therefore, in the present investigation, attempts were made for the exploration of induction of systemic resistance through the use of indigenous fluorescent pseudomonads in the management of black rot disease of cabbage under Gangetic alluvial region of West Bengal. Out of 11 fluorescent pseudomonads, PT1 and PB3 collected from cabbage phyllosphere and rhizosphere, respectively, exhibited highest antagonistic activity against Xcc and were identified as Pseudomonas aeruginosa. Combined application using seed treatment (ST), root dipping (RD) and foliar spray (FS) with PT1 was the best treatment in reducing incidence of disease by 50.6 % followed by statistically at par treatments ST+RD+FS with PB3 and ST+RD with PT1. Activity of phenylalanine ammonia lyase (PAL) and phenol content were found to be negatively correlated with the disease progress at 1 % level of significance in Xcc - cabbage interaction. However, in PT1 treated ISR in cabbage - Xcc system, peroxidase (POX), polyphenol oxidase (PPO) and PAL activity were induced in a higher state and the p-values of these three enzymes indicated higher level of correlation with disease reaction. Therefore, it may be postulated that POX, PAL and PPO are the enzymes associated with the multi-coordinate defence mechanism in Xcc-cabbage interaction under biotic elicitor primed condition.